An Economic History of Malaysia, c.1800-1990 - Drabble, John. author. aut Link
XXIII, 320 p.
Keywords: An Economic History of Malaysia, c.1800-1990 , provides the first general history of the Malaysian economy over the past two centuries, including a survey of the pre-colonial era. A unique feature is that it integrates the historical experiences of Peninsular Malaysia, Sabah and Sarawak as a case study in the onset of modern economic growth. Particular attention is paid to explaining Malaysia's signal success in achieving a relatively smooth shift away from the primary commodity export economy of the colonial period to near-NIC status by 1990.